Evaluation of the detector linearity response of the DR system in different x-ray bean filters - K. A. C. Daros; C. H. Murata; E. M. Policarpo; K. J. Ogawa; C. Miri; O. S. Fontoura; T. M. B. Farias (Brazilian Journal of Radiation Sciences)
In the recent past, at Brazilian radiology services, direct digital radiography (DR) systems are replacing Computed Radiography (CR). This situation provides several significant advantages such as improving digital image quality, patient effective dose reduction, and improved speed of examinations performed. To evaluate DR systems, various organizations have published protocols with guidelines concerning quality assurance and acceptance tests for DRs. In these protocols, there are methodologies for evaluating several parameters, such as the detector linearity response (DLR). To test the DLR, different methodologies are proposed by the organizations, such as the application of different additional filters on the X-ray beams spectrum to promote the X-ray doses suitable to produce the latent image in the DR. The objective of this work was to evaluate the results of different protocol methodologies for carrying out the DLR test of a DR flat panel. An analogic radiology equipment, a primary ionization chamber, a DR system and images unprocessed were used in this study. As indicated by the protocols, the spectra of the X-rays were modified by additional filters of copper (Cu) with aluminum (Al); Al; Cu; and polymethylmethacrylate (PMMA). The spectra of the X-rays were modified to achieve the exposure range of 0.1 to 7 mR. The results showed that the DLR curves adjustment were R²>0.99, for a logarithmic equation, type y=a.ln(x)+b. For the filters of 0.5 mmCu with 1.0 mmAl; 11.5 mmAl; 1.0 mmCu; 21 mmAl the mean pixel values showed 0.9% of the coefficient of variation (COV), while for 10 cm PMMA filters, the COV increased to 2.7%. The study showed that methodologies using Al, Cu and Al with Cu filters DLR have similar responses while using PMMA, the response was slightly different.